Product Reviews by YouTubers: Education or Defamation? - Bunga, Dewi (Kertha Patrika; Vol 43 No 3 (2021)DO - 10.24843/KP.2021.v43.i03.p01, 2021)
One of the contents used by YouTubers to reach subscribers is by conducting product reviews. Based on their competencies, YouTubers convey an assessment of goods and services to the public and as a form of education to the public. This condition has the potential for legal problems if according to the producer or related parties that the results of the assessment by the YouTuber actually drop the goods or services being marketed. In this study, there are two problems discussed, namely, first; criminal policy of insult / and or defamation offenses in cyberspace, second; the principle of truth and public interest as the boundary between education or insulting and / or defamation. This research is a normative juridical method that examines the obscurity of norms regarding insult and / or defamation of product reviews submitted by YouTubers. The criminal policy for insult and / or defamation is regulated in Article 27 paragraph (3) of Law Number 11 of 2008 concerning Electronic Information and Transactions which must be linked to Articles 310 and 311 of the Criminal Code. Testing the principles of truth and public interest is very important to free YouTubers from criminal charges on charges of defamation / and or defamation